From coast to Isle: exploring the morphological diversity of tender coconuts in selected Indian accessions - Diwakar, Y.; Vishnuvardhana; Niral, V.; Halesh, G. K.; Venkatesh, J.; Ramesh, S. V.; Neenu, S. (Journal of Plantation Crops, 2025)
Coconut (Cocos nucifera L.) is an economically and nutritionally important tropical crop, particularly renowned for its oil and tender coconut water, a beverage known for its hydrating properties and health benefits. This study investigates the morphological diversity of tender nuts from various coconut accessions collected from coastal and island ecosystems in India. A total of 31 coconut accessions, including the Indian West Coast Tall (WCT) as a reference, were evaluated for tender nut traits. Significant variability was observed, with tender coconut weights ranging from 831.67 g in Andaman Horned Tall to 2940.83 g in Kodiaghat Brown Tall. Quantity of tender coconut watervaried from 85.55 mL in Andaman Horned Tall to 545.58 mL in Kodiaghat Brown Tall followed byDugong Creek Tall (495.83 mL) and Nicobar Tall AuckChung (485.0 mL). The average TSS was 5.0° Brix, with Andaman Horned Tall recording the highest TSS at 5.98° Brix. Accessions such as Kodiaghat Brown Tall and Dugong Creek Tall demonstrated superior traits, suggesting their potential in varietal breeding programs. The study underscores the genetic diversity present in coconut accessions, with implications for improving tender coconut production. The findings highlight the importance of understanding these traits for developing varieties that meet consumer and market demands, ultimately contributing to the sustainability of coconut.